Environmental quality evaluation of soil from Pernambuco’s recreational park (Brazilian Journal of Radiation Sciences (BJRS), 2018)
Parks and squares are inserted in urban environments, influenced by diverse anthropogenic sources of chemical elements. The Apipucos Maximiano Campos Park, located in the Apipucos neighborhood, in the city of Recife - PE aims to promote entertainment for the local population. The park was previously a green area containing scrap metal, which was removed to build the park, but it is still affected by vehicular emissions. Considering the possibility of negative health effects caused by local contaminants, the concentration of Cu, Fe, Mn, Ni, Pb and Zn in the soil of the Apipucos Maximiano Campos Park was determined by the Energy Dispersive X-Ray Fluorescence (EDXRF) technique. Fifteen soil samples were collected at three locations, under the vertical projection of tree crowns. Before the analysis, the samples were dried in an oven at 60 °C for 24 hours and pulverized. The concentrations of Cu, Fe, and Zn were characteristic of polluted soil; and the concentrations of Ni and Pb were higher than the reference values for Pernambuco. These contaminations probably derived from the previously deposited scrap metal. Such levels of contaminants demand public actions to avoid a negative effect on the health of the local population and to the environment.